2023
DOI: 10.3390/pharmaceutics15030988
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Delivery of Gemcitabine by Estrogen Receptor-Targeted PEGylated Liposome and Its Anti-Lung Cancer Activity In Vivo and In Vitro

Abstract: Lung cancer is one of the main causes of cancer-related deaths. At present, the main treatment method for lung cancer is chemotherapy. Gemcitabine (GEM) is widely applied in lung cancer treatment, but its lack of targeting ability and serious side effects limit its application. In recent years, nanocarriers have become the focus of research to solve the above problems. Here, we prepared estrone (ES)-modified GEM-loaded PEGylated liposomes (ES-SSL-GEM) for enhanced delivery by identifying the overexpressed estr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…Tang et al produced estrone (ES)-modified gemcitabine (GEM)-loaded PEGylated liposomes (ES-SSL-GEM) for enhancing delivery efficiency by identifying estrogen receptors overexpressed on lung cancer A549 cells. The findings showed that ES-SSL-GEM, which has good stability, can reduce drug leakage during blood circulation and enhance tumor-targeted effect [ 31 ].…”
Section: Passive Targeting Targeted Of Drug Deliverymentioning
confidence: 99%
“…Tang et al produced estrone (ES)-modified gemcitabine (GEM)-loaded PEGylated liposomes (ES-SSL-GEM) for enhancing delivery efficiency by identifying estrogen receptors overexpressed on lung cancer A549 cells. The findings showed that ES-SSL-GEM, which has good stability, can reduce drug leakage during blood circulation and enhance tumor-targeted effect [ 31 ].…”
Section: Passive Targeting Targeted Of Drug Deliverymentioning
confidence: 99%
“…As a result of the interaction between the receptor and the linker, HA has the potential to bind to the CD44 receptor, which is overexpressed in certain cancer cells. As a consequence of this, HA-modified nanoparticles have the potential to assist in the diagnosis and treatment of cancer [22][23][24]. Dopamine-modified HA was used to coat the surface of iron oxide nanoparticles in a study carried out by Wang and co-workers [25].…”
Section: Diagnostic Detection and Imaging Applications Of Biopolymeri...mentioning
confidence: 99%